Congruencia de la actividad y perfil investigativo de la Universidad San Gregorio de Portoviejo con las necesidades empresariales del entorno socioeconómico - Soliz Quiroz, Jefferson Santiago (2021)
The main objective of this degree work was to carry out a case study on the university research of the Universidad San Gregorio de Portoviejo (USGP) to determine its congruence with the business needs of the socioeconomic environment. The development began with an interview with the rector of the USGP to obtain information about the agreements that have been signed in the years 2018 - 2019, in addition, observation visits and surveys were made to the research teachers. Later, interviews were applied to key informants of the companies with which they have signed agreements. With these data, a pertinence matrix was elaborated to determine the congruence between the research activity with the teaching profile and the business needs of the socioeconomic environment. As a result, it was obtained that there is a limited number of research professors who are dedicated to developing projects in the business area, 14% of those surveyed are unaware of the agreements that the university maintains; the key informants of the companies indicate that more links should be created with the community and the impact that they have should be measured. On the other hand, there is a low level of congruence in certain profiles because they are directed towards projects that are not related to the knowledge and skills of the research professors; in the same way, there is a low level between the research activity and the business needs because they are not very focused on solving the problems of the environment.